PERANAN KREDIT KETAHANAN PANGAN DAN ENERGI (KKP-E) PADA BANK RIAU KEPRI CABANG BENGKALIS TERHADAP PERKEMBANGAN USAHA NELAYAN (Studi Kasus Nelayan Desa Teluk Pambang Kecamatan Bantan Kabupaten Bengkalis Provinsi Riau) - Jon Budi Prayogo; Zulkarnaini '; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThe research was conducted on 2nd to 18th October 2014 in Teluk Pambang Village, Bantan District, Bengkalis Regency, Riau Province. The purpose of this research was to (1) Know the system and procedure of Energy and Food Security Credit (KKP-E), (2) to analyze the effect of Energy and Food Security Credit (KKP-E) for fisherman’s income in Teluk Pambang Village, (3) to analyze the difference of fisherman’s income in Teluk Pambang Village before and after receiving Energy and Food Security Credit (KKP-E). The method used in this study was a survey method with descriptive data analysis, multiple linear regression analysis and Wilcoxon analysis using SPSS Statistics 17,0.The results showed that systems and procedure Energy and Food Security Credit (KKP-E) consists of the business sector financed, the terms and documents according to the Bank, credit limit, assurance, process analysis and credit approval, monitoring and reporting. Based on multiple linear regression analysis, Energy and Food Security Credit (KKP-E) capital was not positive and significant impact on the income of fishermen. Based on Wilcoxon analysis, fisherman’s income difference significantly before and after receiving Food Security and Energy Credit (KKP-E).Keywords: Energy and Food Securiy Credit (KKP-E), Fisherman’s Income, Teluk Pambang Village